LANGUAGE AND MENTALITY QUESTIONS IN THE MODERN PERIOD - Abbasova, K.Y (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
A study of the features of linguistic processes in modern society has shown that language has a special place in the system of communication and cultural symbolism. Here the role is played by the cognitive and communicative aspects of the speaking person's speech, the nature of the assessment situation and its impact on verbal self-modeling. It is also important to consider the influence of speech behavior on the formation of ethnopsychological qualities of a person. The richness of the vocabulary, especially those associated with folklore, folklore, forms a broad worldview with a special approach to assessing the world around and oneself. It should also emphasize the role of language processes in the formation of the social typology of personality. It is known that many styles of speech are just characteristic of each social group. Hence the differences in the speech behavior of the individual in various social areas of life. Purposeful work is needed to form the necessary social policy of the state in establishing a high culture of speech behavior. Consideration of the patterns of speech behavior of individual peoples in fiction and art as a whole, in everyday life and in the family, in various spheres of life will help to identify cognitive characteristics of the thinking of representatives of this people based on certain linguistic qualities. It is especially important to study the formation of cognitive skills in childhood and young age, as well as in adulthood.